Let's get invisible! - Stine, R. L. (New York : Scholastic, 1993)
Max is thrilled when he discovers a mirror in his attic that can make him invisible, but his fun turns to fright when his disappearances begin to last longer than he wants.
4.3
5-8
Keywords: Fantasy; Mirrors -- Fiction; Mirrors -- Fiction; Fantastic fiction; Fantastic fiction